Pengaruh Word Of Mouth dan Experiential Marketing Terhadap Keputusan Mahasiswa Memilih Berkuliah Di Universitas Merdeka Malang - Zata Aman, Yosanda; Widiawati, Diah; Cendana Wangi, Sekar (Green Publisher Indonesia, 2024)
Education plays a crucial role in individual development, enabling people to learn and apply various knowledge in life. Universitas Merdeka Malang is one of the leading higher education institutions in Indonesia. This research focuses on the campus's indirect marketing strategies to introduce itself to the broader community. Word of mouth communication and experiential marketing can be effective information sources in influencing prospective students. The research aims to analyze the impact of these two factors on the decision to choose Universitas Merdeka Malang as a study destination. The study uses primary data collected from 97 respondents, students of the Faculty of Economics and Business from the 2022-2023 academic year. Samples were selected using random sampling method, and data were analyzed using multiple regression analysis. Research findings indicate that word of mouth and experiential marketing significantly influence the college selection decision.